2020
DOI: 10.1083/jcb.201902114
|View full text |Cite
|
Sign up to set email alerts
|

ER arrival sites associate with ER exit sites to create bidirectional transport portals

Abstract: COPI vesicles mediate Golgi-to-ER recycling, but COPI vesicle arrival sites at the ER have been poorly defined. We explored this issue using the yeast Pichia pastoris. ER arrival sites (ERAS) can be visualized by labeling COPI vesicle tethers such as Tip20. Our results place ERAS at the periphery of COPII-labeled ER export sites (ERES). The dynamics of ERES and ERAS are indistinguishable, indicating that these structures are tightly coupled. Displacement or degradation of Tip20 does not alter ERES organization… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
24
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(29 citation statements)
references
References 64 publications
3
24
0
Order By: Relevance
“…It is possible that the need for long-range tethering is obviated by the close association of ER export and arrival sites. In the yeast Pichia pastoris, this creates bidirectional transport portals at which the Dsl1 complex may be able to capture COPI vesicles as they are budding from the Golgi (49).…”
Section: Discussionmentioning
confidence: 99%
“…It is possible that the need for long-range tethering is obviated by the close association of ER export and arrival sites. In the yeast Pichia pastoris, this creates bidirectional transport portals at which the Dsl1 complex may be able to capture COPI vesicles as they are budding from the Golgi (49).…”
Section: Discussionmentioning
confidence: 99%
“…The question as to where COPI vesicles fuse on the ER has been addressed by expressing (X)FP‐tagged proteins homologous to those belonging to the COPI‐tethering factor complex of mammals. This strategy has been successfully applied to both plants (Lerich et al ., 2012), and more recently in Pichia pastoris (a yeast with a stacked Golgi) (Chowdhury et al ., 2020), and reveals that ERIS lie close to ERES on the ER membrane, that is, immediately underneath the cis ‐cisterna. This indicates that bidirectional transport is restricted to the ER–Golgi interface, and is in accord with the Secretory Unit concept.…”
Section: Er Exit Sites (Eres) Er Import Sites (Eris) and The Assemblmentioning
confidence: 99%
“…COPI and COPII coat proteins appear to concentrate in peripheral and central positions of the ERES cup, respectively. To confirm this complementary distribution, reminiscent of recent findings in the yeast Pichia pastoris (Roy Chowdhury et al, 2020), we examined ERES-Golgi units in fat body expressing Sec13.GFP and γCOP.RFP simultaneously. This confirmed that COPII is found at the center of ERES, whereas COPI occupies preferentially the periphery of the structure (Figure 4A).…”
Section: Resultsmentioning
confidence: 55%
“…Among these, budding of Golgi-bound membrane carriers at ERES is known to involve the COPII coat complex, a set of proteins highly conserved in eukaryotes (Jensen and Schekman, 2011). In these same ERES regions, in addition, traffic in the reverse Golgi-ER direction through COPI vesicles is thought to concentrate as well (Roy Chowdhury et al, 2020). Despite their highly dynamic underlying nature, live imaging has repeatedly shown that ERES are relatively long-lived, stable entities (daSilva et al, 2004; Hammond and Glick, 2000; Shindiapina and Barlowe, 2010; Westrate et al, 2020).…”
Section: Introductionmentioning
confidence: 99%